Effect of Storage Fungi on the Seed Quality Parameters of Different Mustard Varieties (Biological Sciences - PJSIR, 2005)
Seven seed storage fungi (Aspergillus flavus, Alternaria brassicae, Helminthosporium brassicae, Penicillium sp, Pythium sp, Rhizoctonia solani and Fusarium oxysporum) were isolated from four mustard seed varieties (B-raya, Y-raya, B-M-1 and S-9). A. flavus was the most predominant fungus found on seeds of all the four mustard seed varieties. The germination percentage of the fungal infected seeds of B-raya decreased significantly, followed by Y-raya, B-M-1 and S- 9 mustard seed varieties, both in the laboratory and the pot-scale studies. It was noted that weight and oil contents of seeds of all the four varieties decreased in those that were infected by fungi during storage in comparison with the seeds that were stored in sterilized bottles. The fungal infected seeds also had lower glucosinolate and erucic acid contents than those of the non-infected seeds.